Amplification of Seismic Response in Poroviscoelastic Soil Layer. (11th July 2020) - Yang, Liming; Luo, Junhui; Chen, Weiyun; Mou, Yumin
Abstract : The time-dependent behaviour of saturated soils under static and dynamic loading is generally attributed to the flow-dependent and viscous behaviour of pore fluid. However, the intrinsic energy dissipative effects from the flow-independent viscoelastic behaviour of solid skeleton are not always considered. In this study, the effect of flow-independent viscoelastic behaviour on the seismic amplification of ground soil in vertical and horizontal directions is studied based on a two-phase poroviscoelastic model. A generalized Kelvin–Voigt model is used to define the effective stress in the soils, and the compressibilities of both solid skeleton and pore fluid are considered. The seismic-induced dynamic displacements are analytically derived and are shown to depend on soil layer thickness, soil properties, and ground motion parameters. The formulation neglecting the viscoelastic behaviour of solid skeleton could overestimate both the vertical and horizontal motion amplifications at the surface of ground soil. In addition, the seismic responses of viscoelastic soils are demonstrated to be closely related to the saturation state of surface soil.